Alteration in the Gut Microbiota Provokes Susceptibility to Tuberculosis - Khan, Nargis; Vidyarthi, Aurobind; Nadeem, Sajid; Negi, Shikha; Nair, Girish; Agrewala, Javed N. (Frontiers in Immunology, 2016)
Abstract The microbiota that resides in the gastrointestinal tract provides essential health benefits to the host. In particular, they regulate immune homeostasis. Recently, several evidences indicate that alteration in the gut microbial community can cause infectious and non-infectious diseases. Tuberculosis (TB) is the most devastating disease, inflicting mortality and morbidity. It remains unexplored, whether changes in the gut microbiota can provoke or prevent TB. In the current study, we have demonstrated the antibiotics driven changes in the gut microbial composition and their impact on the survival of Mtb in the lungs, liver and spleen of infected mice, compared to those with intact microbiota. Interestingly, dysbiosis of microbes showed significant increase in the bacterial burden in lungs and dissemination of Mtb to spleen and liver. Further, elevation in the number of Tregs and decline in the pool of IFN-γ and TNF-α releasing CD4 T cells was noticed. Interestingly, fecal transplantation in the gut microbiota disrupted animals exhibited improved Th1 immunity and lesser Tregs population. Importantly, these animals displayed reduced severity to Mtb infection. This study for the first time demonstrated the novel role of gut microbes in the susceptibility to TB and its prevention by microbial implants. In future, microbial therapies may help in treating patients suffering from TB.